Last Interglacial Iberian Neandertals as fisher-hunter-gatherers - Zilhão, João (2020)
The origins of marine resource consumption by humans have been much debated. Zilhão et al. present evidence that, in Atlantic Iberia's coastal settings, Middle Paleolithic Neanderthals exploited marine resources at a scale on par with the modern human–associated Middle Stone Age of southern Africa (see the Perspective by Will). Excavations at the Figueira Brava site on Portugal's Atlantic coast reveal shell middens rich in the remains of mollusks, crabs, and fish, as well as terrestrial food items. Familiarity with the sea and its resources may thus have been widespread for residents there in the Middle Paleolithic. The Figueira Brava Neanderthals also exploited stone pine nuts in a way akin to that previously identified in the Holocene of Iberia. These findings add broader dimensions to our understanding of the role of aquatic resources in the subsistence of Paleolithic humans.